Child Development with the D-score - van Buuren, Stef; Eekhout, Iris (Taylor & Francis, 2024)
Children learn to walk, speak, and think at an astonishing pace. The D-score presents a unified framework that places children and their developmental milestones from different tools onto the same scale, enabling comparisons in child development across populations, groups and individuals. This pioneering text explains why we need the D-score, how we construct it, and how we calculate it. It will be of interest not just to professionals in child development, but also to policymakers in international settings and to data scientists. Open Plus Books are published on an F1000-powered open research platform where they can be amended, updated, and extended, in addition to being published as a print and open access ebook. The Open Plus Book version of this book, available at gatesopenresearch.org/dscore, and the Open Access version of this book, available at www.taylorfrancis.com, have been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. For more information about Open Plus Books go to www.routledge.com and for F1000 go to f1000.com.